Principals' support for teachers' working conditions in devolved school settings: Insights from two Australian States. (July 2019) - McGrath-Champ, Susan; Stacey, Meghan; Wilson, Rachel; Fitzgerald, Scott; Rainnie, Al; Parding, Karolina
Shifts in schooling policy have had substantial impact upon the role of principals as well as the relationship that principals have with their teaching staff. In this paper we report on the initiatives 30 principals in a diverse range of devolved Australian government schools adopt to shape and support the local, school-level working conditions of teachers. Surprisingly, principals were commonly unable to articulate – or even respond to – this matter. More commonly principals reported being oriented to lifting capability through a focus on student outcomes, a focus that is consistent with much of the devolution and autonomy rhetoric. Of those who could respond regarding working conditions, dispositions of paternalistic 'care', basic distributive actions or even a lack of influence or control were reported, and clear spatial and social dimensions accompanied these patterns. Given that devolution has recently created new responsibilities for principals in Australian government schools, including in relation to staff, this finding is understandable but none the less holds substantial implications and raises questions about the managerial capacity needed for schools to be sustainable, positive workplaces.